2012
DOI: 10.1080/1068316x.2011.598156
|View full text |Cite
|
Sign up to set email alerts
|

Own-age bias in video lineups: a comparison between children and adults

Abstract: The present study investigated whether child (sixÁeight years of age) and adult witnesses (18Á29 years of age) would exhibit an own-age bias when trying to identify targets from video lineups. One hundred and eighty-six participants viewed two filmed events that were identical, except one starred a child target and one a young adult. After a delay of twoÁthree days each witness saw a lineup for the child and adult target. Children exhibited an own-age bias and were better at correctly identifying the own-age t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
4
10
0
Order By: Relevance
“…Brewer, 2006), this has not been thought to extend to children younger than 12 years (Brewer & Palmer, 2010). Nonetheless, there has been research that found children aged 6-8 years had higher confidence ratings for correct identifications for TP line-ups, than those who did not correctly identify a culprit (Havard, Memon, Laybourn, & Cunningham, 2011). These findings suggest that there may be situations under which a child's confidence can be a reliable indicator of accuracy.…”
Section: Introductionmentioning
confidence: 76%
“…Brewer, 2006), this has not been thought to extend to children younger than 12 years (Brewer & Palmer, 2010). Nonetheless, there has been research that found children aged 6-8 years had higher confidence ratings for correct identifications for TP line-ups, than those who did not correctly identify a culprit (Havard, Memon, Laybourn, & Cunningham, 2011). These findings suggest that there may be situations under which a child's confidence can be a reliable indicator of accuracy.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, as most studies have used a young adult target in their mid-20s (Beresford & Blades, 2006;Dekle et al, 1996;Parker & Carranza, 1989;Parker & Ryan, 1993;Zajac & Karageorge, 2009) this immediately puts children at a slight disadvantage, when it comes to making an identification. One study that looked at the own age bias with child witnesses (aged 6Á8 years) found that correct rejection rates were higher for the similar aged child target (59%), as compared to the adult target (20%), and these rates were more comparable to correct rejection rates made by adult witnesses (Havard, Memon, Laybourn, & Cunningham, 2012).…”
mentioning
confidence: 99%
“…Child participants made more correct identifications and correct rejections of child targets than adult targets while adult participants made more correct identification of child targets over adult targets with no difference in correct rejections of either target. (Harvard C., Memon, Laybourn, & Cunningham, 2012). Within adults, there is no difference in correct identifications or correct rejections of young adults, middle aged adults, and senior adults in identifying a young adult target.…”
Section: Literature Reviewmentioning
confidence: 92%